EFFECT OF ADDING CHLOROGENIC ACID ON BROILER PERFORMANCE, SOME BLOOD BIOCHEMICAL PARAMETERS AND GUT HEALTH - A. T. M. Khishtan; S. A. M’Sadeq; S. S. M. Beski; S. M. Ameen Omar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to evaluate the effectiveness of chlorogenic acid on productive performance, blood biochemistry and intestinal histomorphology of broiler chickens. A total of 256-day old Ross 308 broiler chicks were divided into 4 treatments with 4 replications, 16 chicks per replicate. Treatments were arranged as follow: control group was left without any additive, whereas group 2-4 supplemented with 1, 1.5 and 2 mL of chlorogenic acid per litter of drinking water respectively. Results of this study showed that the body weight gain of birds received chlorogenic acid significantly increased when compared to control group. Lowest feed intake (P<0.05) was recorded for the birds received 1.5ml of chlorogenic acid than other experimental groups. Better feed conversion ratio was found in birds offered 1 and 1.5 mL chlorogenic acid compared to the control and those offered 2 mL /L of chlorogenic acid. The chlorogenic acid significantly increased villous heights and reduced crypt depths. The higher villous surface area was recorded for the birds received 1 mL of chlorogenic acid (P<0.05) than other groups. The birds in control group significantly increased the serum content of globulin over all treatments. It can be concluded that chlorogenic acid had a positive effect on performance and gut health of broiler chickens.